THE EFFECT OF GREEN HUMAN RESOURCE MANAGEMENT ON EMPLOYEE PERFORMANCE WITH WORK ENVIRONMENT AS MODERATION VARIABLE - Rieneke Ryke Kalalo (Adisam Publisher, 2024)
Backgrounds Researchers believe that the activities included in the scope of Green Human Resource Management can have a positive relationship and a significant influence on employee performance because by improving these activities, employees' personalities will become better trained in carrying out responsibilities regarding the environment, and can pay more attention. important things in more detail, and ultimately can improve employee performance. Objectives Therefore, this research aims to analyze the influence of Green Human Resource Management on Employee Performance. Different from a number of other studies, this research adds the Work Environment variable as a moderating variable. Methods: This research is a quantitative research with an exploratory approach which uses the previous issues surrounding Green Human Resource Management, Employee Performance and the Work Environment as stepping stones to find separate elements of novelty in each topic and unite them into elements of new novelty and different from previous research . The data in this research uses primary data that researchers obtained from Suzuki employees spread throughout Indonesia. The data that researchers obtained was distributed using the online questionnaire method and analyzed using the smart PLS 4.0 analysis tool. Results and Conclusions: the Green Human Resource Management variable can have a positive relationship direction and a significant influence on Employee Performance because the P-Values value is below the significance level of 0.05 namely 0.019.. Apart from this, there is a second hypothesis of researchers who believe that the Work Environment variable can moderate the influence of the Green Human Resource Management variable on employee performance because a comfortable and safe environment can make the green resource green management program help to influence employee performance more significantly. In line with this statement, the results of the second row of the third table of the Path Coefficient show more significant results, namely 0.000 below 0.05, which is more significant than the direct test of 0.019. Thus, the first and second hypotheses in this research can be confirmed and accepted.